Does serum prostate specific antigen levels correlate with the prostatic inflammation in elderly patients without clinically proven prostate cancer? - Çolakerol, Aykut; Temiz, Mustafa Zafer; Boran, Çetin; Bastug, Yavuz; Kandirali, Engin (The European Research Journal, 2022)
Objectives: To determine the whether histological prostatic inflammation correlates with serum prostate specific antigen (PSA), free PSA (fPSA) and percent of fPSA (%fPSA) levels in elderly patients without clinically proven prostate cancer. Methods: A total of 115 patients without clinically proven prostate cancer with transrectal prostate biopsy were included in this retrospective study. Patients were divided two main groups as patients with and without histologic prostatic inflammation. A grading of the histological prostatic inflammation was performed and patients with prostatic inflammation were divided into three subgroups. The age, prostate volume, serum PSA, fPSA and %fPSA levels were compared between patients with and without prostatic inflammation. Correlation between the parameters and grade of prostatic inflammation was also investigated. Results: Serum PSA and %fPSA levels were significantly higher in men with histologically proven prostatic inflammation (15.47 ± 15.28 ng/mL vs. 11.67 ± 8.12 ng/mL; p = 0.002 and 19.8 ± 0.7 vs. 15.79 ± 0.9; p = 0.01, respectively). The mean serum PSA levels were significantly different among the subgroups (p = 0.02) and prostatic inflammation correlated positively with the PSA levels (r = 0.320, p < 0.001). Conclusions: Our findings suggested that reporting the grade of prostatic inflammation in elderly patients may help avoiding unnecessary repeat biopsies if elevated serum PSA level is the only indication for initial prostate biopsy.